Perbandingan Kinerja Keuangan Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Sebelum dan Saat Pandemi Covid-19 - Lia Rahmawati; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The purpose of this study is to compare the financial performance of healtcare sector companies listed on the IDX before and during the Covid-19 pandemic. The type of data used is secondary data in the form of company financial report data for the 2018-2021 period. The research method used is a comparative descriptive method with a quantitative approach. The sampling technique used was purposive sampling. Financial performance is measured using the CR, TATO, DAR, DER, ROA and REO. Hypothesis testing using Paired sample t-test and Wilcoxon Match Pair Test. The test results show that there is no significant difference in financial performance before and during the pandemic when measured by TATO, DAR, DER, ROA, and ROE. Meanwhile, if measured by CR, it shows that there is a significant difference between financial performance before and during the covid-19 pandemic.